2015
DOI: 10.1016/j.jclinepi.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of search strategies for systematic reviews: validation showed the noninferiority of the objective approach

Abstract: To the best of our knowledge, our findings indicate for the first time that the objective approach for the development of search strategies is noninferior to the conceptual approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 27 publications
2
68
0
Order By: Relevance
“…The objective approach applied by the German Institute for Quality and Efficiency in Health Care (IQWiG) in systematic searches is based on a structured procedure [8][9][10] and is already well established in the development of search filters [4]. The objective approach comprises the following steps [8,10]: generation of a test set (relevant references from, e.g., systematic reviews), division of the test set into development and comparator sets, development of the search strategy with references from the development set (analyzing information derived from the titles, abstracts and subject headings of relevant references with text-mining tools such as Wordstat [11]; see the IQWiG guidance in Appendix A), and validation of the search strategy (checking whether references from the comparator set can be identified with the search strategy developed beforehand) [9]. To identify previous systematic reviews in the area of interest, the information specialist or project manager conducts a preliminary search in bibliographic databases such as the Cochrane Library or MEDLINE.…”
Section: Introductionmentioning
confidence: 99%
“…The objective approach applied by the German Institute for Quality and Efficiency in Health Care (IQWiG) in systematic searches is based on a structured procedure [8][9][10] and is already well established in the development of search filters [4]. The objective approach comprises the following steps [8,10]: generation of a test set (relevant references from, e.g., systematic reviews), division of the test set into development and comparator sets, development of the search strategy with references from the development set (analyzing information derived from the titles, abstracts and subject headings of relevant references with text-mining tools such as Wordstat [11]; see the IQWiG guidance in Appendix A), and validation of the search strategy (checking whether references from the comparator set can be identified with the search strategy developed beforehand) [9]. To identify previous systematic reviews in the area of interest, the information specialist or project manager conducts a preliminary search in bibliographic databases such as the Cochrane Library or MEDLINE.…”
Section: Introductionmentioning
confidence: 99%
“…Taking a text mining approach could help researchers to more objectively identify potential articles for structured or systematic reviews on particular challenges of societal importance (e.g., see (Hausner et al, 2015), who tested highly structured automated text searches in support of systematic reviews in the medical sciences) or the development of new types of horizon scanning exercises (e.g., Small et al, 2014) that expand on current expert-based efforts in environmental science (Sutherland et al, 2011(Sutherland et al, , 2016 or apply horizon scanning initiatives to other societal challenges. A dictionary-based approach also permits for comparisons of textual data from other than Web of Science across sources or times.…”
Section: Discussionmentioning
confidence: 99%
“…Having multiple coders would also allow tests of inter-coder reliability. Alternatively, the development of a completely objective approach to dictionary development of a search strategy might be warranted as they can be as accurate as those developed in conjunction with subject experts (Hausner et al, 2015).…”
Section: Limitationsmentioning
confidence: 99%
“…As mentioned in the title of our article [5], our study specifically refers to the development of search strategies for systematic reviews. In our understanding, Grant et al [6] identified 14 different types of reviews, including systematic ones.…”
Section: "The Calculation Of the Relative Recall Rates Are Only Reflementioning
confidence: 99%
“…As mentioned in the introduction and Section 3.3. of our article [5], we did not add study filters to the search strategies, as the objective approach is applied only in those parts of the strategy where no validated filters are used (eg, population, intervention).…”
Section: "According To the Approach Of Hausner Et Al They Have To Admentioning
confidence: 99%